Komposisi tubuh dan karakteristik kebugaran fisik atlet pencak silat elit Indonesia - Haris Nugroho; Satria Yudi Gontara; Gatot Jariono; Ronny Saifullah (Universitas Nusantara PGRI Kediri, 2025)
Optimizing performance and devising efficient training regimens requires understanding elite athletes' physical profiles. In Indonesian Pencak Silat, BMI and body fat percentage reveal athletes' physical readiness and competitive advantages. Therefore, this study aims to examine the physical condition of Indonesian elite Pencak Silat athletes by assessing their BMI and body fat percentage. This research employed a quantitative descriptive design. A total of 20 elite athletes (12 males and 8 females) were selected through purposive sampling based on their achievements at national and international championships. Data collected included gender, weight class, BMI, and body fat percentage, measured using standardized anthropometric procedures. The data were analyzed using descriptive statistics, partial correlation analysis, and one-way ANOVA to explore relationships and differences based on gender and weight categories. The study found that athletes had a normal BMI of 22.8 kg/m² (SD = 1.9) and a body fat percentage of 16.5% (SD = 4.2%). On average, male athletes had a lower body fat percentage (14.2%) than female athletes (19.8%), a significant difference (p < 0.05). BMI was not significantly different among weight classes. However, partial correlation analysis showed a slight positive association (r = 0.45) between BMI and body fat percentage. In conclusion, Indonesian elite Pencak Silat athletes had ideal body compositions, with gender variances in body fat. These findings underline the need for gender and weight-specific training and dietary programs. This study contributes evidence-based recommendations to support more effective athlete development frameworks for advancing Indonesian Pencak Silat globally.